A critical review on the progress of MQL in machining hardened steels. Issue 4 (2nd October 2022) - Sultana, Nazma; Dhar, N. R.
ABSTRACT: Due to their increased hardness, hardened steels are referred to as difficult-to-cut metals. Machining such hardened steels (hard machining) is preferred since it minimizes process stages and processing time. However, severe machining in dry conditions needs larger specific energy for metal removal, reducing tool life dramatically at higher velocities which affect the product quality as well. Cutting fluids influence machinability through cooling, lubricating, and washing away chips. Excessive usage of cutting fluids harms the environment, economy, and operators' health. Researchers are so focusing on MQL as a sustainable green cooling alternative to potentially damaging conventional cooling approaches.In this current work, MQL was initially introduced with its core ideas and functions. As a follow-up, the application of MQL in various machining techniques especially for hardened steel was discussed. A complete evaluation of the various modes of MQL was presented, along with its advantages and disadvantages. According to studies, using NFs as a coolant and lubricant has grown more popular than any other way due to its superior performance in temperature control, improved surface quality, and low environmental threat. Finally, this article provides easy-to-follow instructions on how to use MQL in various ways to improve the machinability of hardened steel.